Bulk and surface modified polycrystalline CuWO4 films for photoelectrochemical water oxidation. (February 2023) - Lee, Jin Uk; Kim, Jeong Hun; Kang, Kyungwoong; Shin, Yun Seop; Kim, Jin Young; Kim, Jin Hyun; Lee, Jae Sung
Abstract: Polycrystalline CuWO4 film is an emerging photoanode material for photoelectrochemical (PEC) water splitting with a small bandgap to absorb visible light and excellent stability in a neutral electrolyte. However, its PEC performance is quite low mainly due to its poor charge transfer characteristics. To enhance the performance of the CuWO4 photoanode, two modification strategies are employed; SnO2 as an electron transfer layer to improve the bulk charge separation efficiency of CuWO4 and cobalt phosphate as a co-catalyst to augment the surface charge separation efficiency at the interface of CuWO4 ||electrolyte. The two modifications enhance the PEC activity two times to 0.13 mA/cm 2 @ 1.23 VRHE for water oxidation and 0.24 mA/cm 2 @ 1.23 VRHE for hole scavenger oxidation, and exhibit an excellent stability in a neutral electrolyte. Although the performance is still very low compared to well-developed metal oxide photoanodes, this work shows possibility of further improvement with further developments of synthesis method as well as applying other elaborate modification strategies. Graphical abstract: Image 1